Letter to society: what are we doing to the environment that sustains us? (Research, Society and Development, 2024)
In recent decades, attention has increasingly focused on the impact of human disturbances on the degradation of natural ecosystems, primarily due to the need to "supply" food, housing, and consumer goods for the human population. Human activities have intensified the effects of climate change, which are considered the main drivers of biodiversity loss, economic, and social damage. Thus, it can be argued that the capitalist system, based on fossil fuels and the forest resources exploitation, is chiefly responsible for the current ecological crisis. This “document” aimed to present a letter to society about what we are doing to our ecosystems, serving as a warning for the existence of our specie. The methodology used in the preparation of the study was a narrative literature review.